Peculiarities of content and trends in the dynamics of public perceptions of war and victory - SLYUSAREVSKYY, Mykola (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2024)
Background. This study is relevant due to the significant dependence of the moral and psychological state of the troops in a belligerent country and the success of combat operations on the perception of the war and its end in the public consciousness, as supported by scientific sources. The purpose of this article is to reconstruct the primary content characteristics and dynamic trends of war and victory images in the Ukrainian public consciousness, along with highlighting the factors that influence their formation. Methods. The research was conducted through secondary analysis of data from two monitoring studies: one focused on the state of public consciousness, with a questionnaire consisting of psychosemantic descriptors, and another addressing public opinion related to pressing socio-political issues. These studies are conducted annually by the Institute of Social and Political Psychology of the National Academy of Pedagogical Sciences of Ukraine, utilizing a sample that represents the adult population of Ukraine aged 18 and older (1,200 respondents were interviewed). Results. The study reveals that the perception of war in public consciousness is complex and not merely a sensory experience. It is shaped by various factors, including historical family experiences, literary and documentary representations, and media portrayals of the current conflict. Since the onset of the Russian invasion, the predominant image of the Russian-Ukrainian war has emerged as a struggle of the people against occupiers. This image is reinforced by diverse elements within public consciousness, although some perspectives can weaken this prevailing narrative. Ambiguities in the war’s progression and inconsistent messages from state leadership have led to a diversification of attitudes regarding the anticipated victory, blending militaristic and pacifist sentiments from the Soviet era. Conclusions. Based on the analysis, the author draws practical conclusions advocating for a reformatting of public perceptions concerning war and Victory, freeing them from elements of pacifism and unrealistic expectations; raising society’s tolerance for uncertainty; and proactively developing strategies and technologies to mitigate the negative psychological effects of unfulfilled expectations, which may pose a significant risk to social stability in the postwar period.